Causal Association Between Tea Consumption and Bone Health: A Mendelian Randomization Study - Chen, Song; Chen, Tianlai; Chen, Yibin; Huang, Dianhua; Pan, Yuancheng; Chen, Shunyou (Frontiers in Nutrition, 2022)
Abstract Background: Much observational research reported that tea consumption decreases the risk of osteoarthritis (OA), rheumatoid arthritis (RA), and osteoporosis (OP) which are the three major bone disorders. However, the observed correlation is inconclusive. To determine the causal relationship between genetically predicted tea intake and OA, RA, and OP, we performed a two-sample Mendelian randomization (MR) study based on large samples. Methods: The European population's genome-wide association meta-analysis (GWAS) dataset identified SNPs associated with tea consumption was obtained from Neale Lab’s analysis of UK Biobank data that comprised 349,376 participants of European ancestry. We extracted genetic data for knee OA (17,885 controls and 4462 cases), hip OA (50,898 controls and 12,625 cases), and RA (43,923 controls and 14,361 cases) from the UKBiobank and OP cases (93083 controls and1175 cases) from FinnGen Data Freeze 2. A Mendelian randomization (MR) study was conducted to examine the effect of selected single nucleotide polymorphisms (SNPs) and OA, RA, and OP risk. Several sensitivity analyses were performed with weighted median and inverse-variance weighted methods for estimating the causal effects. Results: In this MR study, the genetically predicted per one cup increase of tea consumption was associated with knee OA (OR: 1.30 (95%CI:1.13-1.50)) using IVW with random effect. Genetic predisposition to tea consumption was not associated with hip OA (OR:1.17, 95% CI: 0.97-1.41), RA (OR:1.20, 95%CI:1.02-1.40) and OP (OR:1.25, 95%CI:0.82-1.90). Following the sensitivity analysis, there was no potential pleiotropy and heterogeneity. Conclusion: According to our study, there was a positive causal relationship between tea consumption and the risk of knee OA, RA, and this major causal effect did not found at hip OA and OP.